Azad Sherni - Adamson, Joy; Translated by Mehmood Sham (Islambad National Book Foundation, 2018)
Continues the story of Elsa, the lioness, and her cubs. Includes the death of Elsa and a new life for the cubs in the Serengeti Reserve.
Include Illustrations
Keywords: Elsa -- Elsa -- (Lion) -- Lion -- Kenya -- Biography. -- Lion